Perancangan Buku Pop-up Tema Pertemanan guna Mencegah Bullying dalam Proses Pembelajaran di Kelas - Maharani, Anastacia Ruth; Haryadi, Toto (Jurnal Ilmiah Multimedia dan Komunikasi, 2024)
Bullying is a hostile act that is deliberately carried out by irresponsible individuals or group to hurt or threaten so that the victim feels sad, scared, and traumatized. Bullying can happen anywhere, one of which is in the State Elementary School of Sumberagung 2 Bojonegoro environment. To educate about bullying, it is necessary to design attractive learning media so that it is easy to understand and attracts students' focus. Pop-up book has the potential to solve this problem because it has attractive elements in it. The 3-dimensional pages that can move when opened are an added point in creating a more enjoyable learning process. The research method used is qualitative descriptive, which supported by data analytic method of 5W + 1H and the Design Thinking method for creative process, which produces the main media in the form of pop-up books and supporting media in the form of banners, posters, drawstring bags, and stickers. This design is expected to be able to help minimize the problem of bullying that occurs at SDN Sumberagung 2 Bojonegoro, especially in grade 1 students.